Plant Development and Organogenesis: From Basic Principles to Applied Research - Frugis, Giovanna (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The way plants grow and develop organs significantly impacts the overall performance and yield of crop plants. The basic knowledge now available in plant development has the potential to help breeders in generating plants with defined architectural features to improve productivity. Plant translational research effort has steadily increased over the last decade due to the huge increase in the availability of crop genomic resources and Arabidopsis-based sequence annotation systems. However, a consistent gap between fundamental and applied science has yet to be filled. One critical point often brought up is the unreadiness of developmental biologists on one side to foresee agricultural applications for their discoveries, and of the breeders to exploit gene function studies to apply to candidate gene approaches when advantageous on the other. In this book, both developmental biologists and breeders make a special effort to reconcile research on the basic principles of plant development and organogenesis with its applications to crop production and genetic improvement. Fundamental and applied science contributions intertwine and chase each other, giving the reader different but complementary perspectives from only apparently distant corners of the same world.